Governança do executivo brasileiro: efeitos da relação entre política e burocracia, ou como o presidente dorme tranquilo à noite - Haína Coelho Pereira da Silva (2018)
Does the relationship between politcs and bureaucracy matter for ministerial performance? This dissertation aims to find empirical and theoretical fundaments that different presidential strategies of portfolio allocation produce impact on ministerial performance. Ministerial Performance is conceptualized as execution of Executive goals, and measured by annual proportion of ministeries financial execution. Mymain hypothesis is that Supervised Command - when a bureaucrat executive- secretary is allocated to monitor a partisan ministry - would present better levels of performance when compared to other kinds of Command. The mechanism behind this argument is the presidents control over the ministry through the executive- secretary. I also argue that bureaucracy quality has effect over the ministerial Commands capacity of influencing that agencys performance. Empirical tests were enacted on a panel database with ministery/year observations, for all Brazilian Executive ministeries from 2000 to 2014. Results achieved through ANOVA, linear regression with fixed/random effects, and regression on matched data models, show the situation is opposite to the main hypothesis. Supervised Command gives the worst means of ministerial performance, in rebuttal to the Partisan Command, with the best means. Bureaucracy quality, despite not having much effect overperformance alone, bears some influence over Commands effect, but only when low. Education background of the public service, as a proxy for bureaucracy quality, had more effect than statutories proportion. The main conclusion obtained from this dissertation: control, predicted in the theory of delegation and its perils, even though is a political goal to be pursued, not necessarily reflects in administrative efficiency. Monitoring seems to work more as a deadlock than a way to provide better results. However, since I dont evaluate the quality of the goals execution, its not possible to affirm if the financial execution means the policy was actually executed, or if it was the way it should be